Effects of Trigger Point Dry Needling on Strength Measurements and Activation Levels of the Gluteus Medius: A Quasi-Experimental Randomized Control Study - Eric Schneider; Elizabeth S. Moore; Rob Stanborough; Emily Slaven (North American Sports Medicine Institute, 2022)
# Background Latent trigger points have been identified as a source of impaired muscle function giving rise to a reduction in force production and alterations in muscle activation patterns and movement efficiency. There is limited investigation into the effectiveness of a treatment in reducing these clinical manifestations. # Purpose To investigate whether the application of trigger point dry needling (TDN) to latent trigger points within the gluteus medius musculature affected strength measurements and muscle activation levels immediately following intervention. # Design Quasi experimental, single group, pretest-posttest, randomized control study # Methods A control and an intervention side were randomly assigned for each participant (_N_ = 39). Hand held dynamometer (HHD) force measurements and raw surface electromyography (sEMG) amplitude readings were recorded during maximal volitional isometric contractions of the gluteus medius in two separate positions before and after application of TDN. Comparison of within and between group data were conducted. # Results A statistically significant interaction between time (pre-TDN to post-TDN) and groups (intervention side and control side), _p_ < 0.001 was found for HHD measurements in both positions. Post hoc analysis revealed a statistically significant difference (_p_ < 0.001) for all comparisons in the side lying neutral (SL0) position, while statistically significant differences (_p_ < 0.001) were found for pre and post-TDN measurements within intervention side as well as between the intervention and control side for post-TDN measurements in the side lying internal rotation (SLIR) position. For sEMG amplitude measurements, statistically significant differences were found only in the SL0 position for within group comparisons on the intervention side (_p_ = 0.009) and for between group comparisons for post-TDN measurements (_p_ = 0.002). # Conclusion Application of TDN to latent trigger points within the gluteus medius can significantly increase gluteus muscle force production immediately following intervention while reducing the level of muscle activation required during contraction. # Level of Evidence Level 2